A mass spectrometry and DFT study of pyrithione complexes with transition metals in the gas phase. (5th September 2017) - Butler, Matias; Cabrera, Gabriela M.
Abstract: 2‐Mercaptopyridine N ‐oxide (pyrithione, PTOH) along with several transition metal ions forms coordination compounds displaying notable biological activities. Gas‐phase complexes formed between pyrithione and manganese (II), cobalt (II), nickel (II), copper (II), and zinc (II) were investigated by infusion in the electrospray source of a quadrupole‐time of flight mass spectrometer. Remarkably, positive ion mode spectra displayed the singly charged metal adduct ion [C10 H8 MN2 O2 S2 ] 2+ ([M(PTO)2 ] + or [M(DPTO)] + ), where DPTO is dipyrithione, 2, 2′‐dithiobis(pyridine N ‐oxide), among the most abundant peaks, implying a change in the oxidation state of whether the metal ion or the ligands. In addition, doubly charged ions were recognized as metal adduct ions containing DPTO ligands, [M(DPTO)n ] 2+ . Generation of [M(PTO)2 ] + / [M(DPTO)] + could be traced by CID of [M(DPTO)2 ] 2+, by observation of the sequential losses of a charged (PTO + ) and a radical (PTO ) deprotonated pyrithione ligand. The fragmentation pathways of [M(PTO)2 ] + / [M(DPTO)] + were compared among the different metal ions, and some common features were noticed. Density functional theory (DFT) calculations were employed to study the structures of the observed adduct ions, and especially, to decide in the adduct ion [M(PTO)2 ] + / [M(DPTO)] + whether the ligands are 2 deprotonated pyrithiones or a single dipyrithione as well as the oxidation state of the metal ion in the complex. Characterization of gas‐phase pyrithione metal ion complexes becomes important, especially taking into account the presence of a redox‐active ligand in the complexes, because redox state changes that produce new species can have a marked effect on the overall toxicological/biological response elicited by the metal system.